The Directional Drill Monitor for Long Hole Gas Drainage in Coal Mines (The Australasian Institute of Mining and Metallurgy, 1992)
The Directional Drill Monitor (DDM) is an advanced instrument for real time in hole surveying. It was developed by Du Pont (Australia) to suit Australian gassy coal mining conditions. The instrument consists of three units: i. Down hole transmitter ii. Acoustic transducer iii. Data receiver processor unit (i.e. up hole unit). This paper describes the function of each unit in detail and highlights the importance of the DDM in long hole drilling efficiency. Surveying is carried out independent of hole depth. Each survey takes 2-3 minutes to complete, the frequency of surveying to control borehole trajectory is determined by the accuracy required for a particular hole.